(untitled) (JED (Jurnal Etika Demokrasi), 2021)
Abstract: The purpose of this study was to obtain empirical data about the relationship between students’ understanding of the Unitary Republic of Indonesia (Unitary State of the Republic of Indonesia) and the state defense attitude at SMK Al-Bahri Bantar Gebang. This research was conducted on grade X students of Al-Bahri Bantar Gebang Vocational School. The research method used was quantitative descriptive method with correlation study approach. The sample in this study was taken randomly using the Proportional Random Sampling technique with a sample size of 40 respondents. The instrument used was a multiple choice test for variable X and a questionnaire with the type of attitude scale for variable Y. The reliability test results for variable X were 0.968 (0.968> 0.444) and Y variable were 0.965 (0.965> 0.444). Hypothesis testing is done using Pearson’s product moment formula. Obtained r count 0.656 with r table 0.312 (0.656> 0.312). Thus it can be concluded that there is a positive relationship between students’ understanding of the Homeland with the attitude of defending the country. Keyword: Understanding, Unitary Republic of Indonesia, Defending the Nation Abstrak: Tujuan penelitian ini adalah untuk memperoleh data empiris tentang hubungan pemahaman peserta didik tentang NKRI (Negara Kesatuan Republik Indonesia) dengan sikap bela negara di SMK Al-Bahri Bantar Gebang. Penelitian ini dilakukan pada peserta didik kelas X SMK Al-Bahri Bantar Gebang, Metode penelitian yang digunakan adalah metode deskriptif kuantitatif dengan pendekatan studi korelasi. Untuk sampel dalam penelitian ini diambil secara acak menggunakan teknik Proporsional Random Sampling dengan jumlah sampel 40 responden. Instrumen yang digunakan adalah berupa tes pilihan ganda untuk variabel X dan angket dengan jenis skala sikap untuk variabel Y. Hasil uji realiabilitas variabel X sebesar 0,968 (0,968 > 0,444) dan variabel Y sebesar 0,965 (0,965 > 0,444). Pengujian hipotesis dilakukan dengan menggunakan rumus product moment pearson. Diperoleh r hitung 0,656 dengan r tabel 0,312 (0,656 > 0,312). Dengan demikian dapat disimpulkan bahwa terdapat hubungan positif antara pemahaman peserta didik tentang NKRI dengan sikap bela negara. Kata Kunci : Pemahaman, Negara Kesatuan Republik Indonesia, Bela Negara